Strategic leaders' ecosystem vision formation and digital transformation: A motivated interactional lens - Reuter, Emmanuelle; Steven Floyd (My University, 2023)
The question of why and how strategic leaders differ in the ecosystems they envision is central to firms' digital transformation. We unpack the cognitive microfoundations of how strategic leaders form their ecosystem vision—a mental model of a firm's multilateral complementarities with its partners to realize a value proposition. Our motivated interactional lens emphasizes the role of strategic leaders' cognitive motivation for shaping four interaction types with (prospective) partners: participatory, selective, collaborative, and reclusive. We theorize how these interactions shape the changes strategic leaders make in their mental models, and thus, to envision different levels and types of complementarities with (prospective) partners in the digital transformation. Our theory illuminates the roles of strategic leaders, their cognitive motivations, and social interactions in firms' ecosystem leadership. Managerial Summary: Digital transformation is an ecosystem challenge for incumbent firms. As part of their ecosystem leadership, strategic leaders need to form a vision of how to complement their value offerings with (prospective) partners' offerings. This vision, in turn, can affect the types of ecosystems they enact. We develop a theoretical model that emphasizes the role of strategic leaders' cognitive motivation for the interactions they engage in with (prospective) partners and for the types of ecosystem visions they form as a result.